Bootstrap estimation of the average household expenditure or personal care and effects at regional level - Jachelle Anne G. Dimapilis (2013)
This study explored the use of bootstrap in estimating households' expenditure on personal care and effects at regional level. Bootstrap yields superior estimates compared to the estimates of simple random sampling without replacement (SRSWOR). Bootstrap estimates have lower variance than SRSWOR estimates. Furthermore, bootstrap estimates have smaller bias compared with SRSWOR estimates.
Keywords: Sampling (Statistics); Bootstrap estimation